(untitled) (Biological Sciences - PJSIR, 2023)
In developing countries, cold chain facilities are not present in all areas. Ultra-high temperature (UHT) milk is usually manufactured in these countries for catering the needs of all areas. In UHT treatment, sterile milk is filled in sterile packages in a sterilized environment. The operation is usually performed at 140 °C to destroy vegetative forms of bacteria. Shelf life of UHT milk very high as compared to raw milk at room temperature without the need of cold storage. However, UHT treatment and subsequent storage lead to several undesirable biochemical reactions such as alteration in the structure of whey proteins, formation of Maillard reaction products and lipid oxidations etc. Proteolytic events in milk consequences in the production of bitter flavour and age gelation, which is led to limit the life of UHT treated milk. Alkaline proteinase, plasmin are the proteolytic enzymes of milk origin, while psychrotrophic bacteria also produce extracellular proteinases which causes breakdown of protein in ultra-high temperature milk. In UHT milk, sedimentation can happen right after thermal treatment or it takes place during the storage time. Sediment is composed of denatured protein, minerals, lactose and lipids with wide variation in composition. Degree of sedimentation depends upon the raw milk quality, processing and storage temperature.